A NEW ELECTRON SPECTROSCOPY SYSTEM FOR MEASURING ELECTRON EMISSION FROM FAST ION INTERACTIONS WITH ATOMIC, MOLECULAR, AND CONDENSED PHASE TARGETS - Hawkins, Wilson L (East Carolina University, 2016)
A new electron spectroscopy system has been developed for measuring electron emission from gas and solid targets induced by fast ion impact. This system uses an ultrahigh-vacuum compatible cylindrical deflector analyzer, designed and fabricated in the Department of Physics at East Carolina University, to measure electron yields as a function of electron energy and emission angle for fast ions interacting with materials. The new spectroscopy system was tested in a previously existing high-vacuum target chamber that has been installed on a new beam line in the ECU Accelerator Laboratory. In addition to the new analyzer, a new data acquisition and experimental control system, based on LabVIEW computer control software, was developed and tested using an existing cylindrical mirror analyzer. Data from this system was compared to previous results to confirm the functionality of the design. Subsequently, the new analyzer was installed in the high-vacuum target chamber and tested by measuring Auger electron emission from 2 MeV protons incident on an argon gas target and comparing to well-known emission spectra. Ultimately, the new electron spectroscopy system will be used for measuring electron yields from condensed phase targets in ultrahigh-vacuum conditions in future experiments.
Keywords: Auger Electrons; Fast Ion Interactions; Particle Accelerator; Electrostatic analyzers; Electron spectroscopy; Electrons--Emission